An empirical model for the travel distance prediction of deflection-type rock avalanches in the wenchuan earthquake area - Yang, Hailong; Pei, Zuan; He, Zhihao; Lei, Jin; Xia, Xiaotian (Frontiers in Earth Science, 2022)
Travel distance is a significant indicator for evaluating the mobility of rock avalanches and is usually used to identify the approximate delineation of potentially endangered regions. The deflection-type rock avalanche is a typical laterally confined rock avalanche and is characterized by obvious changes in the travel path. In this study, we selected deflection-type rock avalanches that occurred in the Wenchuan earthquake area as the research object and statistically analyzed 54 rock avalanches collected from the literature. Multiple linear regression of the logarithm of the ratio of slope height to movement distance (h/L) versus the logarithm of other parameters was developed to obtain a best-fit empirical model for the travel distance prediction of deflection-type rock avalanches. The validity of the proposed empirical model was verified by the satisfactory agreement between observations and predictions. Moreover, the effect of local topography on the mobility of deflection-type rock avalanches is also discussed using regression analysis.